2008
DOI: 10.1002/poc.1318
|View full text |Cite
|
Sign up to set email alerts
|

Ring‐chain interconversion of sulforhodamine‐amine conjugates involves an unusually labile CN bond and allows measurement of sulfonamide ionization kinetics

Abstract: AbstractpH‐dependent interconversion between ring and chain forms of sultams/sulfonamides derived from conjugates of sulforhodamines with amines, and the associated sulfonamide ionization, have been studied by a combination of equilibrium and kinetic methods. The colorless, ring‐closed sultam form is favored at alkaline pH with an apparent pKa of 7.37 for the color change of the methylamine conjugate of Sulforhodamine B. The ring‐closed form is also favored at very low pH (apparent pKa ∼ 0.68) by protonation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…At the start of our work, the sulforhodamines were converted to their sulfonyl chlorides using phosphoryl chloride alone [2] but we later found that addition of a little phosphorus pentachloride gave more efficient conversion (overnight at room temperature). In either case the crude reaction mixtures, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At the start of our work, the sulforhodamines were converted to their sulfonyl chlorides using phosphoryl chloride alone [2] but we later found that addition of a little phosphorus pentachloride gave more efficient conversion (overnight at room temperature). In either case the crude reaction mixtures, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The dipyrrolidinylsulforhodamine 4 was available from previous work [11]. Crystals of the sulforhodamines and the derived sultams had strong tendencies to retain solvent (see examples in previous data for 4 [11] and its derived N-methylsultam [2]) and we were generally unable to obtain satisfactory microanalysis data. Therefore only HRMS data are reported to verify elemental composition but the NMR spectra (apart from traces of residual solvent) contained no extraneous peaks.…”
Section: General Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…The ortho rhodamine B isomer exhibits much more complete quenching behavior at high pH compared to ortho-Texas Red [30,32]. Additionally, the ortho isomer of rhodamine B exhibits pHsensitive fluorescence in a more acidic pH range and is far less expensive than Texas Red.…”
Section: Introductionmentioning
confidence: 97%